2006
DOI: 10.1093/beheco/arl092
|View full text |Cite
|
Sign up to set email alerts
|

Facultative response to a kleptoparasite by the cooperatively breeding pied babbler

Abstract: In many cases of interspecific kleptoparasitism, hosts develop defensive behaviors to minimize the impact of kleptoparasites. Because vigilance and defensive behaviors are often costly, selection should favor hosts that adjust the amount of investment needed to minimize losses to kleptoparasitism. However, examples of such facultative responses are rare. Here, we investigate the response of cooperatively breeding pied babblers (Turdoides bicolor) to the drongo (Dicrurus adsimilis), an avian kleptoparasite that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 28 publications
5
122
1
Order By: Relevance
“…Animals commonly eavesdrop on the alarm calls of other species in their environment [6,24,25] and drongos appear to exploit this behaviour by using deceptive alarm calls to steal food from target species [16]. These deceptive alarm calls are likely to work because the cost to target species of ignoring drongo true alarms is greater than the cost of responding to false alarms [9,26].…”
Section: Discussionmentioning
confidence: 99%
“…Animals commonly eavesdrop on the alarm calls of other species in their environment [6,24,25] and drongos appear to exploit this behaviour by using deceptive alarm calls to steal food from target species [16]. These deceptive alarm calls are likely to work because the cost to target species of ignoring drongo true alarms is greater than the cost of responding to false alarms [9,26].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted observations and experiments between 16 March and 3 June 2009, on the Kuruman River Reserve, southern Kalahari desert, South Africa (26858 0 S, 21849 0 E) (see Ridley & Raihani 2007a for ecological details). We observed eight colour-ringed groups of pied babblers habituated to close (less than 5 m) observation on foot (median group size ¼ 5, range 3-12).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a lack of predator activity, a locally abundant food source or the lessening of predation risk owing to weather, cover or habitat type could lead to both a relaxation of vigilance and a tendency for heterospecific individuals to gather. Among birds, fork-tailed drongos are known to be associated with reduced sentinel behaviour in small (but not large) pied babbler groups (Ridley & Raihani 2007), and both downy woodpeckers and whitebreasted nuthatches are less vigilant when foraging in mixed-species flocks. Downy woodpeckers reduced their vigilance when played the contact calls of heterospecific flock members (Sullivan 1984), and both species increased vigilance after the removal of two flocking species (Dolby & Grubb 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether 'eavesdropping' provides wider benefits by allowing an individual to reduce its vigilance. Although several researchers have noted a relationship between the presence of heterospecific co-foragers and vigilance (Rasa 1983;Ridley & Raihani 2007), most of these relationships have not been tested experimentally to ascertain causality, and may relate to confounding variables, such as food availability, habitat type, weather, or predator density. Only in two species, the downy woodpecker (Picoides pubescens) and the white-breasted nuthatch (Sitta carolinensis), has it been demonstrated that individuals reduce their vigilance in response to the presence of heterospecific avian co-foragers (Sullivan 1984;Dolby & Grubb 1998).…”
Section: Introductionmentioning
confidence: 99%